A holistic methodology for hydrokinetic energy site selection. (1st July 2022) - Fouz, D.M.; Carballo, R.; López, I.; Iglesias, G.
Highlights: A holistic methodology for hydrokinetic energy exploitation site selection is proposed. The novel Integrated Hydrokinetic Energy (IHE) index is developed. The IHE index is applied to the Shannon Estuary. The optimum areas for hydrokinetic energy exploitation are identified. Abstract: Hydrokinetic energy can contribute to diversify and decarbonise the energy mix in many coastal regions, in particular estuaries. These are typically areas of high environmental value and with intense socioeconomic activity. The aim of this work is to provide a comprehensive methodology for selecting the optimum locations for hydrokinetic energy exploitation, by considering all the relevant aspects which affect the decision-making process, and improve the current available procedures. The methodology is centred around a novel holistic index, the Integrated Hydrokinetic Energy (IHE) index, which considers: (i) the exploitable resource, (ii) the costs of installation, and (iii) the socioeconomic and environmental aspects. The approach is illustrated through a case study in the Shannon Estuary, on the west coast of Ireland. It is shown that the application of this methodology facilitates the planning and reduces the uncertainties in the development of a hydrokinetic farm project.